Effect Of Cupping Therapy for Low Back Pain (LBP) In Lecturer Of Mandala Waluya University - Lisnawati, Lisnawati; Nofitasari, Nofitasari; Ari, Ari; Islaeli, Islaeli; Yusnayanti, Cici; Masriwati, Sitti (Journal of Islamic Nursing, 2024)
Cupping therapy is a complementary treatment option that can be administered to individuals suffering from Low Back Pain (LBP), a condition that continues to see a rise in its prevalence year after year. LBP is frequently experienced by office professionals who spend extended periods working in a seated position, which can lead to reduced productivity and a decline in overall health. The objective of this research was to assess the impact of cupping therapy on LBP among lecturers at Mandala Waluya University. This research entails a quantitative approach, employing a quasi-experimental one-group pre and post-test design. The research population comprises all lecturers at Mandala Waluya University, totaling 166 individuals, with a sample size of 30 respondents selected through purposive sampling techniques, as determined by the Lameshow formula. The study's findings indicate that 80.8% of the total sample of Mandala Waluya University lecturers between the ages of 30-40 years suffer from LBP. Through paired t-test analysis, it was established that the phi value was 0.000, which is smaller than the alpha value. Consequently, cupping therapy has the capacity to alleviate pain in LBP patients by promoting muscle relaxation and stimulating the release of beta hormones, which, in turn, reduces pain. Cupping therapy demonstrates its effectiveness in alleviating LBP and enhancing the daily functioning of lecturers at Mandala Waluya University.